Potential of deep seawater mariculture for economic transformation in Sabah, Malaysia - Marziah, Z.; Azhim, Azran; Mahdzir, A.; Musa, M. N.; Jaafar, A. B. (2015)
A Malaysian state of Sabah is blessed with natural deep sea water (DSW). The presence of these DSW's offers a potential for OTEC power plant to be installed and operated using warm surface sea water (SSW) as a heat source and the cold DSW as a heat sink. In the operation, the power plant may need to spend a considerable amount of power to pump up the DSW. The cold DSW, after serving its function as coolant to the condenser of the power plant, apparently appears as cold waste-water and may pose a disposal problem to the environment. However, being very rich in nutrients, the used DSW instead create another valuable potential for secondary commercial activities in industries like mariculture, pharmaceutical, cosmetic, medicinal, temperate crop farming, district cooling, etc. all of which, if fully developed could offer a real economic transformation for the state of Sabah, as that experience by the Japanese Kumejima of Okinawa prefecture. This paper focuses on the discussion on the potential of DSW in enhancing the development of Sabah mariculture industry, party contribution towards accelerating the socioeconomic transformation of the state and the people.